Influence Quality Service Employee To Loyalty Customers at BRI Bank Tassililu Unit Subdistrict West Sinjai - Irwan Abdullah; Syarifuddin Sulaiman; Nurul Ainul Mukrima; Kahar (Income Journal Of Economics Development, 2025)
This study aims to analyze the influence of service quality on customer loyalty at Bank BRI Tassililu Unit. The research was conducted with a sample of 87 respondents, using 24 items divided into two variables: service quality as the independent variable (15 items) and customer loyalty as the dependent variable (9 items). The collected data were analyzed using SPSS 26. The results of the t-test indicate that the service quality variable has a t-value of 16.604, which is greater than the critical value of 1.663, with a significance level of 0.000 (<0.05). These findings confirm that service quality has a positive and significant effect on customer loyalty. Each dimension of service quality—tangibility, reliability, responsiveness, assurance, and empathy—plays a crucial role in enhancing customer satisfaction, which ultimately strengthens their loyalty to the bank. This study highlights the importance for Bank BRI Tassililu Unit to continuously improve service quality to maintain customer trust and satisfaction. Providing excellent service not only fosters customer loyalty but also encourages positive word-of-mouth recommendations, which can attract new customers. Additionally, future research is suggested to explore other influencing factors such as brand image, customer satisfaction, and perceived value to gain a more comprehensive understanding of customer loyalty determinants in the banking sector.